2012
DOI: 10.2166/wcc.2012.145
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of faecal indicator organisms in a temperate river during storm conditions

Abstract: Greater incidence of storm events, which can lead to greater contamination of surface waters by human and animal faeces, are a predicted feature of climate change in parts of Europe and elsewhere. The aim of theis study was to combine the use of a novel quantitative microbial source tracking (QMST) method with established water quality monitoring procedures during an intense summer storm event in a rural UK catchment, to establish dominant sources of faecal pollution. One-litre grab samples of river water were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 77 publications
1
1
0
Order By: Relevance
“…Our analyses of sewage samples showed the presence of all the three phage types, with levels of SOMCPH and phages of GB-124 similar to those reported earlier from untreated sewage ( Ebdon et al, 2012 ; Dias et al, 2015 , 2018 ; Purnell et al, 2015 , 2016 ; McMinn et al, 2017 ). As expected, phages of GB-124 were present at lower concentrations than SOMCPH in sewage ( Payan et al, 2005 ; Blanch et al, 2006 ; Ebdon et al, 2007 , 2012 ; Nnane et al, 2012 ; Harwood et al, 2013 ; McMinn et al, 2014 ; Diston and Wicki, 2015 ) and were consistent with concentrations reported from Europe and United States of 3.90 log 10 PFU/100 mL and 2.58 log 10 PFU/100mL, respectively. The SOMCPH concentrations we detected in sewage in Kolkata were also similar to the concentrations observed in Europe [approx.…”
Section: Discussionsupporting
confidence: 87%
“…Our analyses of sewage samples showed the presence of all the three phage types, with levels of SOMCPH and phages of GB-124 similar to those reported earlier from untreated sewage ( Ebdon et al, 2012 ; Dias et al, 2015 , 2018 ; Purnell et al, 2015 , 2016 ; McMinn et al, 2017 ). As expected, phages of GB-124 were present at lower concentrations than SOMCPH in sewage ( Payan et al, 2005 ; Blanch et al, 2006 ; Ebdon et al, 2007 , 2012 ; Nnane et al, 2012 ; Harwood et al, 2013 ; McMinn et al, 2014 ; Diston and Wicki, 2015 ) and were consistent with concentrations reported from Europe and United States of 3.90 log 10 PFU/100 mL and 2.58 log 10 PFU/100mL, respectively. The SOMCPH concentrations we detected in sewage in Kolkata were also similar to the concentrations observed in Europe [approx.…”
Section: Discussionsupporting
confidence: 87%
“…[7] The model parameters reflect the characteristics of Cryptosporidium parvum oocysts, a waterborne pathogen behind several notable outbreaks of waterborne disease and a subject of many studies [see, e.g., Atherholt et al, 1998;Atwill et al, 2006;Dai and Boll, 2006;Dorner et al, 2006;Searcy et al, 2006]. Cryptosporidium, like many other microbes and chemicals, is heterogeneously distributed in the environment, its transport is driven by random events, it has a low infectious dose and is expensive to monitor [Curriero et al, 2001;Gale, 1998;Nnane et al, 2012;Richardson et al, 1991;Yeghiazarian et al, 2009]. For these reasons, the decision-making process aiming to reduce human exposure to this, and many other pathogens and contaminants, must ultimately rest with mathematical models capable of capturing its occurrence and transport.…”
Section: Introductionmentioning
confidence: 99%